CYBER PUBLIC RELATIONS STRATEGY IN ANTICIPATING THE PANDEMIC EFFECTS ON CAFÉ BUSINESS: The Case of #ngopidirumah Movement by Anomali Coffee - Devita, Marliani; Kania, Dessy (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
The COVID-19 pandemic triggered the #ngopidirumah movement, which was campaigned on social media by Anomali Coffee as a local coffee shop to adjust consumers' lifestyles during quarantine at home implementing Cyber ​​Public Relations (CPR). This article analyzes the performance of CPR in the #ngopidirumah movement on Instagram during the COVID-19 pandemic. The research method used is the case study approach, with data obtained through in-depth interviews, digital observation, and documentation. The findings show that the implementation of CPR by Anomali Coffee in the #ngopidirumah movement on Instagram makes it easy to access information for consumers who still want to enjoy cafe-style coffee at home. It suits CPR principles, namely Transparency, Internet Porosity, The Internet as An Agent, Richness in Content and Reach. This effort also positively impacts building good relations between Anomali Coffee and consumers in cyberspace during the pandemic. To cite this article (7th APA style):Devita, M. & Kania, D. (2020). Cyber Public Relations Strategy in Anticipating the Pandemic Effects on Café Business: The Case of #ngopidirumah Movement by Anomali Coffee. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), xx-xx. http://dx.doi.org/10.36782/jcs.v10i2.2101